الإتصال التنظيمي وعلاقته بالأداء الوظيفي بالمؤسسة - بن حنيش خالد; الجوزي وهيبة (University of Eloued جامعة الوادي, 2024)
ملخص: هدفت هذه الدّراسة إلى محاولة إبراز وجود علاقة من عدمها بين الإتصال التنظيمي في مديرية التربية وأحد الظواهر التنظيمية ألا وهي الأداء الوظيفي وذلك من خلال دراسة ميدانية أجريت بمديرية التربية بولاية الوادي ، وقد استخدمت الدراسة المنهج الوصفي كما استهدفت فئة الموظفين والعمال كون هتين الفئتين المكون الرئيسي لمجتمع البحث وإذ يقعون بصورة مباشرة تحت تأثير ظاهرة الإتصال التنظيمي ، حيث توصلت الدراسة إلى وجود علاقة بين الإتصال التنظيمي والإداء الوظيفي. Abstract: This study aimed to try to highlight the presence or absence of a relationship between organizational communication in the Directorate of Education and one of the organizational phenomena, namely job performance, through a field study conducted in the Directorate of Education in the State of El Oued. The study used the descriptive approach and also targeted the category of employees and workers, since these two categories are the main components of society. The research falls directly under the influence of the phenomenon of organizational communication, as the study concluded that there is a relationship between organizational communication and job performance
Keywords: الإتصال التنظيمي; الأداء الوظيفي; organizational communication; job performance